TEACHING READING COMPREHENSION USING GROUP DISCUSSION - Rizwan, Muhamad; Rachmijati, Cynantia (IKIP Siliwangi, 2021)
English as the first foreign language in Indonesia has important learn. Some aspects in leaning English cover listening, speaking reading and writing. All aspects are crucial for learners to be mastered thus, reading can be the essential aspect of all. In English reading, the difficulties that occur during the lesson is the activity. It is necessary for teachers to establish a good reading activity to cover the teaching and learning activity. The author implemented group discussion to answer the problem in reading activity. The research is established by quantitative method quasi experimental design with pre test and posttest as the instrument of the research. The population is seventh grade students of SMP Negeri 4 CikalongWetan and the sample is 30 students of 7 A as experiment class and 30 students of 7 B as control class. The data collected is analyzed by SPSS using Mann Whitney U test with 0.05 level of significance. The result shows value of significance is 0.010 which is less than 0.05 coefficient level (0.010<0.05) which shows that the null hypothesis is rejected. In conclusion, there is significant difference between students’ reading comprehension in both class.Key Words : Group Discussion, Reading Comprehension